Síntese, caracterização e ensaios biológicos de nanopartículas metálicas e bimetálicas - Santos, Marconi da Cruz [UNIFESP] (2016)
Magnetic iron oxide nanoparticles (NPs) have been used in biomedical applications such as hyperthermia, drug carriers and as a contrast agent in magnetic resonance imaging. In this research, we synthesized and characterized iron oxide NPs (Fe3O4) and bimmetalic NPs Fe@Au. The syntheses of Fe3O4 were performed by coprecipitation of the salts FeCl3.6H2O and FeCl2.4H2O in aqueous media, by thermal decomposition of iron (III) acetylacetonate, Fe(acac)3, in organic medium, as well as by the polyol method in biocompatible organic solvent. In addition, Fe@Au was obtained by microemulsion method in reverse micelle. The functionalization of the NPs' surface with biocompatible molecules containing thiol groups (SH), cysteine (Cys) and glutathione (GSH) and the further nitrosation of its SH groups allowed the formation of S-nitrosothiol groups (S-NO) in the NPs' surface, which enables using these systems as nitric oxide (NO) carriers. The functionalization efficiency measurements of the thiolated NPs' surface were performed using Ellman?s reagent and a slightly acidified sodium nitrite solution (NaNO2) to nitrosate the SH groups in NPs' surface. By means of amperometric measurements we could detect and measure the NO releasing from nitrosated NPs. The structural, morphological and magnetic characterization showed spherical morphologies with low polydispersity in solid state, cubical structures compatible with magnetite. In order to improve biocompatibility and dispersion of these NPs in water, NPs' surface was coated with polyethylene glycol (PEG) beyond thiolated coatings (Cys and GSH). We evaluated the cytotoxicity of PL-Fe3O4-PEG and PL-Fe3O4-PEG-GSH in culture of tumor cells.